The Effectiveness of Virus Material Booklets as Teaching Material Supplements to Increase Students' Interest in Learning - Ginting, Grace Sintya Br; Harini, Nugrahaningsih Wahyu (Journal of Biology Education, 2022)
This study aims to test the validity of the Virus Material Booklet as a teaching material supplement and to test the effectiveness of the booklet in increasing the learning interest of class X students. This research is included in R&D research with a 4D model but only up to 3 stages or 3D. This research was conducted at SMA Negeri 1 Tigapanah in class X MIPA 1 and X MIPA 3, which consisted of 30 students and 15 students. Instruments in the form of validation sheets and measurement sheets of increasing student interest in learning. The results of the test of the validity of the virus material booklet are in the valid category to be used as a teaching material supplement, but in terms of increasing interest in learning the booklet has not been effective because the increase in student interest in learning is in the low category.